2005
DOI: 10.1002/marc.200500239
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Macroporous PMMA/Silica Nanocomposite Monoliths in Supercritical Carbon Dioxide

Abstract: Summary: Macroporous monoliths consisting of silica nanoparticles embedded in poly(methyl methacrylate) (PMMA) were synthesized in supercritical CO2. Well‐dispersed silica particles, pretreated with functional 3‐(trimethoxysilyl)propyl methacrylate (MPS), were to form colloidal PMMA nanocomposites followed by a sol‐gel transition forming interconnected structures resulting in micron‐sized pores with specific areas between 1 and 7 m2 · g−1. SEM and TEM results revealed uniform morphological characteristics of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Thus supercritical CO 2 has frequently been employed as a processing solvent to reduce viscosity and to accelerate the mixing of reagents into the polymer. 12 As for polymer-silica nanocomposites, the use of supercritical CO 2 has been studied for macroporous poly(methyl methacrylate)-silica, 13 polypropylene-silica, 14 poly(vinyl acetate)-silica, 15 polystyrenesilica 16 and polypyrrole-silica 17 systems. We have focused on the fact that some Si(OR) 4 species and CO 2 become a homogeneous mixture under high pressure.…”
mentioning
confidence: 99%
“…Thus supercritical CO 2 has frequently been employed as a processing solvent to reduce viscosity and to accelerate the mixing of reagents into the polymer. 12 As for polymer-silica nanocomposites, the use of supercritical CO 2 has been studied for macroporous poly(methyl methacrylate)-silica, 13 polypropylene-silica, 14 poly(vinyl acetate)-silica, 15 polystyrenesilica 16 and polypyrrole-silica 17 systems. We have focused on the fact that some Si(OR) 4 species and CO 2 become a homogeneous mixture under high pressure.…”
mentioning
confidence: 99%
“…1). The as‐synthesized ZrO 2 particles were not dispersible in CO 2 but were dispersed after modification with MPTMS, which is due to the favorable interaction between MPTMS molecules and CO 2 17. The procedure involved in the preparation of PMMA/ZrO 2 hybrid composite consisted of two steps.…”
Section: Resultsmentioning
confidence: 99%
“…Though few studies have been reported based on the polymer/polymer composites, reports on the synthesis of polymer/inorganic oxide composites in scCO 2 are scarce in the literature. Yue et al synthesized macroporous monoliths consisting of silica nanoparticles embedded in poly(methyl methacrylate) (PMMA) via a one step sol–gel process in scCO 2 17. Recently, PMMA/SiO 2 ,18 PS/C 60 ,19 PVAc/SiO 2 20 and PS/SiO 2 21 nanocomposites were also synthesized in scCO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The TiO 2 particles could be dispersed in scCO 2 after modification with the silylating agent -MPS, which is due to the favorable interaction between -MPS molecules and CO 2 . 17 Polymerization reactions were carried out with varying ratio of TiO 2 nanoparticles (5% to 15% w/w to P3OT) to 3-octylthiophene in supercritical carbon dioxide. The apparent physical nature of P3OT changed remarkably after composite formation.…”
Section: Resultsmentioning
confidence: 99%